Normal and tangential extraction of embedded anchor plates from precast façade concrete panels. (1st March 2016) - Poveda, E.; Ortega, J.J.; Ruiz, G.; Porras, R.; Carmona, J.R.
Highlights: Study of technological anchorages in precast concrete façade elements for buildings. Study of technological anchorages in precast concrete façade elements for buildings. Experimental, analytical and numerical results of anchor plates extraction. Optimisation to give recommendations for design to ensure structural reliability. Abstract: This paper presents a study of steel anchors in precast façade concrete panels subjected to normal and tangential extraction forces. It focuses on four types of inexpensive non-certified anchorages, fairly used in the precast concrete industry, but not properly covered by design standards. The experimental programme consists of twenty-four extraction tests that are used to validate a three-dimensional fracture model by comparing both load–displacement curves and extraction crack-patterns. Experimental and numerical extraction loads are also compared with the ones resulting from analytical design methods for anchorages under the European Standard ETAG 001, while discussing the problems of their application to these non-certified anchorages. Finally, we perform an extensive parametric analysis on the anchor plate extraction resistance. The distance of the plate to the edge of the panel resulted the most influential factor.